Gruppenaufnahme
Vorsitzender Ministerrat der UdSSR Nikolai Tichonow; Außenminister UdSSR Andrej Gromyko; Generalsekretär KPdSU Leonid Breschnew; Ministerpräsident Sowjetunion Alexej Kossygin; Bundesaußenminister Hans-Dietrich Genscher; Bundeskanzler Helmut Schmidt;deutscher Botschafter in Moskau Hans-Georg Wieck;